Reliability and Quality of Complex Systems - B.S. Beysembaeva; V.D. Ezhizhanskiy; A.E. Yarkin; E.A. Aseev; N.S. Reuta (Надежность и качество сложных систем)
Background. The problem of heat sink is one of the main difficulties in ensuring the reliability and quality of complex electronic systems. The heat generated during the operation of electronic devices negatively affects its characteristics, reduces the service life of the device and increases the number of failures. There are various methods and means to combat this phenomenon. Materials and methods. This article presents an overview analysis of some existing thermal management systems. They are compared according to such characteristics as the maximum power of the dissipated heat flow and the type of coolant used. Results and conclusions. Efficient cooling not only increases the service life of the device, but also ensures more stable operation, which can lead to increased productivity and fewer failures. Therefore, choosing the right cooling method is a key factor in ensuring the reliability and quality of electronic equipment.